Choice, Social Structure, and Crime - Barnum, Timothy C. (Crime & delinquency, 2025)
On May 22 to 23, 2023, a workshop held at the Max Planck Institute for the Study of Crime, Security and Law explored the gap between macro-level sociological perspectives and micro-level rational choice perspectives in criminology. The current special issue is the fruit of that effort. Three main themes—structural and cultural constraints, economic opportunities and criminal justice involvement, and moral and ethical contexts—are examined in seven empirical contributions. Together, the studies underscore the notion that while rational choice and sociological theories are often viewed as conflicting and examined separately, they are in fact compatible, and even complementary, aspects of larger social processes. Future research is encouraged to adopt a comprehensive approach encompassing both micro and macro explanations.